Optical laminate and image display device using the same
By using the phase differential layer containing the liquid crystal -oriented solid layer in the optical layer, and through the control of the thickness deviation of the adhesive layer and the curing contraction rate, the problem of uneven display in the image display device is solved, and a more uniform display display is achieved. Effect.
Patent Information
- Application Number
- CN202411005689.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-27
- Filing Date
- 2024-07-25
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, the optical laminated body including the liquid crystal orientation curing layer has a problem of uneven display in the image display device, especially in different visual recognition environments, where pink thin lines may be conspicuous.
The optical layer stack of polarizer containing the polarizer and the adhesive layer layer is composed of the first and second LCDs to the curing layer. The thickness deviation and curing contraction rate ensure T × S ≤ 17 to inhibit the interference of the optical layer.
Effectively suppress the particularly uneven problems in the image display device, especially in the reflection under the 3 wavelength light source, avoiding the pink fine lines in the direction of the bias absorbing axis.
Smart Images

Figure CN119376003A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an optical layered body and an image display device using the optical layered body. Background Art
[0002] In recent years, image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices (such as organic EL display devices, inorganic EL display devices) have rapidly become popular. In image display devices, an optical laminate containing a phase difference film (for example, an anti-reflection film formed by integrating a polarizer and a phase difference film) is used in most cases. In recent years, as the demand for thinning of image display devices has increased, the demand for thinning of optical laminates has also increased. For the purpose of thinning of optical laminates, the thinning of phase difference layers (phase difference films) that contribute greatly to thickness is being promoted. As a representative example of a thin phase difference film, a film (hereinafter referred to as a liquid crystal film) formed by orienting a liquid crystal compound and fixing its orientation state can be cited. Liquid crystal compounds have a particularly large birefringence (Δn) compared to resins, so the thickness of the liquid crystal film that can be used to obtain the desired in-plane phase difference is particularly small compared to the stretched film of the resin film. However, image display devices using an optical laminate including a liquid crystal film may cause display unevenness (specifically, a phenomenon in which thin lines with a particularly conspicuous pink color are visually recognized in the absorption axis direction of the polarizer) depending on the visual environment.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2014-222282 Summary of the invention
[0006] Problems to be solved by the invention
[0007] The present invention has been made to solve the above-mentioned conventional problems, and a main object of the present invention is to provide an optical laminate including a liquid crystal alignment solidified layer and capable of suppressing specific display unevenness when applied to an image display device.
[0008] Means for solving problems
[0009] [1] An optical laminate according to one embodiment of the present invention comprises a polarizing plate including a polarizer and a phase difference layer laminated on the polarizing plate via an adhesive layer, the phase difference layer comprising a first liquid crystal orientation solidification layer and a second liquid crystal orientation solidification layer in order from the polarizing plate side, the phase difference layer as a whole has a circular polarization function or an elliptical polarization function, and has a relationship of Re(450)<Re(550)<Re(650), and the thickness deviation of the adhesive layer in a 10 cm×10 cm area is less than 0.16 μm.
[0010] [2] Another embodiment of the optical laminate of the present invention comprises a polarizing plate including a polarizer and a phase difference layer laminated on the polarizing plate via an adhesive layer, the phase difference layer comprising a first liquid crystal orientation solidification layer and a second liquid crystal orientation solidification layer in sequence from the polarizing plate side, the phase difference layer as a whole has a circular polarization function or an elliptical polarization function, and has a relationship of Re(450)<Re(550)<Re(650), when the thickness of the adhesive layer is set to T(μm) and the curing shrinkage rate of the adhesive constituting the adhesive layer is set to S(%), T×S≤17 is satisfied.
[0011] [3] In the above [2], the thickness variation of the adhesive layer in a region of 10 cm×10 cm is 0.16 μm or less.
[0012] [4] In any one of the above [1] to [3], the adhesive layer is composed of an active energy ray-curable adhesive.
[0013] [5] In any one of the above [1] to [4], the thickness of the first liquid crystal alignment solid layer is 1.7 μm or less.
[0014] [6] According to another aspect of the present invention, there is provided an image display device comprising the optical layered body according to [1] to [5] above.
[0015] Effects of the Invention
[0016] According to the embodiment of the present invention, it is possible to realize an optical laminated body which includes a liquid crystal alignment solidified layer and can suppress specific display unevenness when applied to an image display device. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a schematic cross-sectional view of an optical layered body according to one embodiment of the present invention.
[0018] Description of Reference Numerals
[0019] 10 Polarizer
[0020] 11 Polarizer
[0021] 12 protection layers
[0022] 13 protective layer
[0023] 20 phase difference layer
[0024] 21 first liquid crystal alignment solidification layer
[0025] 22 second liquid crystal alignment solidification layer
[0026] 30 adhesive layers
[0027] 100 optical laminates DETAILED DESCRIPTION
[0028] Hereinafter, representative embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0029] (Definition of terms and symbols)
[0030] The definitions of terms and symbols in this specification are as follows.
[0031] (1) Refractive index (nx, ny, nz)
[0032] “nx” is the refractive index in the direction where the refractive index in the plane is maximum (ie, the slow axis direction), “ny” is the refractive index in the direction orthogonal to the slow axis in the plane (ie, the fast axis direction), and “nz” is the refractive index in the thickness direction.
[0033] (2) In-plane phase difference (Re)
[0034] "Re(λ)" is the in-plane phase difference of the film measured at 23°C using light of wavelength λnm. For example, "Re(550)" is the in-plane phase difference of the film measured at 23°C using light of wavelength 550nm. Re(λ) can be calculated by the formula: Re = (nx-ny) × d, when the thickness of the film is set to d (nm).
[0035] (3) Retardation in the thickness direction (Rth)
[0036] "Rth(λ)" is the phase difference in the thickness direction of the film measured at 23°C using light of wavelength λnm. For example, "Rth(550)" is the phase difference in the thickness direction of the film measured at 23°C using light of wavelength 550nm. Rth(λ) can be calculated by the formula: Rth = (nx-nz) × d, when the thickness of the film is set to d (nm).
[0037] (4) Nz coefficient
[0038] The Nz coefficient is calculated by Nz=Rth / Re.
[0039] (5) Angle
[0040] When an angle is mentioned in this specification, unless otherwise specified, the angle includes angles in both clockwise and counterclockwise directions.
[0041] A. Optical laminate
[0042] Figure 1It is a cross-sectional schematic diagram of an optical laminate of one embodiment of the present invention. The optical laminate 100 shown in the figure has a polarizer 10 and a phase difference layer 20. The polarizer 10 and the phase difference layer 20 are laminated with the aid of an adhesive layer 30. The polarizer 10 typically includes a polarizer 11 and protective layers 12 and 13 arranged on both sides of the polarizer 11. Depending on the purpose, at least one of the protective layers 12 and 13 can also be omitted. Therefore, the polarizer can be a so-called double-sided protective polarizer, a so-called single-sided protective polarizer, or can be composed of a polarizer alone. In one embodiment, the polarizer can be a single-sided protective polarizer in which the protective layer 13 is omitted.
[0043] The phase difference layer 20 includes a first liquid crystal orientation solidification layer 21 and a second liquid crystal orientation solidification layer 22 in sequence from the polarizer 10 side. The first liquid crystal orientation solidification layer 21 and the second liquid crystal orientation solidification layer 22 are stacked with the aid of any appropriate adhesive layer (not shown: hereinafter, sometimes referred to as an interlayer adhesive layer). By using a liquid crystal orientation solidification layer as a phase difference layer, the desired in-plane phase difference can be achieved with a thickness that is extremely thin compared to the stretched film of the resin film. As a result, a significant thinning of the optical laminate can be achieved. The phase difference layer 20 as a whole (as a stack of the first liquid crystal orientation solidification layer 21 and the second liquid crystal orientation solidification layer 22) has a circular polarization function or an elliptical polarization function, and has a relationship of Re(450)<Re(550)<Re(650). In one embodiment, the phase difference layer as a whole, its Nz coefficient can be, for example, 0.30 to 0.70. It should be noted that in this specification, a "liquid crystal orientation solidification layer" refers to a layer in which a liquid crystal compound is oriented in a prescribed direction within a layer and its orientation state is fixed. The “liquid crystal alignment solidified layer” is a concept including an alignment solidified layer obtained by curing a liquid crystal monomer.
[0044] In one embodiment of the present invention, the thickness deviation of the adhesive layer 30 in an area of 10 cm×10 cm is less than 0.16 μm. The thickness deviation is preferably less than 0.13 μm, more preferably less than 0.10 μm, further preferably less than 0.07 μm, particularly preferably less than 0.05 μm, and particularly preferably less than 0.03 μm. The smaller the thickness deviation, the more preferred, and its lower limit can be, for example, 0.01 μm. Such a range of thickness deviation can be achieved, for example, by adjusting the formulation of the adhesive constituting the adhesive layer (substantially the number, type, combination, blending amount, etc. of monofunctional components and multifunctional components), and / or adjusting the coating method of the adhesive. The adhesive constituting the adhesive layer is described in item D below. As the coating method of the adhesive, gravure coating and slit die coating are preferably listed.
[0045] In another embodiment of the present invention, when the thickness of the adhesive layer 30 is T (μm) and the curing shrinkage of the adhesive constituting the adhesive layer 30 is S (%), the thickness T and the curing shrinkage S satisfy the following formula.
[0046] T×S≤17
[0047] T×S is preferably less than 15, more preferably less than 13, further preferably less than 10, particularly preferably less than 8, and particularly preferably less than 7. The lower limit of T×S can be, for example, 2, and can also be, for example, 3. T×S can be an indicator of thickness deviation. If T×S is in such a range, thickness deviation can be well suppressed. If only the thickness T is reduced, problems related to adhesion (such as peeling) often occur. If only the curing shrinkage S is reduced, the elastic modulus of the adhesive becomes larger (the adhesive becomes harder), and as a result, stress relaxation during impact becomes insufficient and peeling is prone to occur.
[0048] The optical layered body may be a combination of the above-described embodiments. That is, in the optical layered body, the thickness deviation may be less than or equal to the above-described predetermined value, and T×S may be less than or equal to the above-described predetermined value.
[0049] While studying the further thinning of an optical laminate containing a liquid crystal orientation solidification layer as a phase difference layer, the present inventors discovered the following new topic: an image display device using an optical laminate containing a liquid crystal orientation solidification layer as a phase difference layer sometimes produces specific display unevenness depending on the visual recognition environment. Specifically, it was found that in the reflection under a three-wavelength light source, a phenomenon (sometimes referred to as linear unevenness) may occur in which a particularly conspicuous pink thin line is visually recognized as a whole in the absorption axis direction of the polarizer. Furthermore, the present inventors conducted an in-depth study on the suppression of such linear unevenness, and found that linear unevenness can be suppressed by suppressing the interference of the optical laminate. In addition, the present inventors found that by making the thickness deviation in a specified area of the adhesive layer less than 0.16 μm, and / or making the thickness T of the adhesive layer and the curing shrinkage S of the adhesive constituting the adhesive layer satisfy the relationship of T×S≤17, the interference of the optical laminate can be suppressed, and as a result, the linear unevenness can be well suppressed, thereby completing the present invention. That is, the effect of the embodiment of the present invention solves the problem newly discovered when studying the further thinning of the optical laminate containing the liquid crystal alignment solidification layer as the phase difference layer, which is an unexpected excellent effect. It should be noted that it is self-evident that the embodiment of the present invention can suppress the display unevenness recognized in the past.
[0050] The adhesive layer 30 is typically composed of an active energy ray-curable adhesive. Active energy ray-curable adhesives have the advantages of excellent adhesion, durability (for example, inhibiting peeling under high temperature and / or high humidity environments) and productivity. The thickness T of the adhesive layer is preferably less than 1.8 μm, more preferably less than 1.5 μm, further preferably less than 1.2 μm, particularly preferably less than 1.0 μm, and particularly preferably less than 0.8 μm. The lower limit of the thickness T of the adhesive layer can be, for example, 0.3 μm. The curing shrinkage S of the adhesive constituting the adhesive layer 30 is preferably less than 15%, more preferably less than 12%, further preferably less than 11%, and particularly preferably less than 9%. The lower limit of the curing shrinkage S can be, for example, 3%, and can also be, for example, 5%. If the thickness T and the curing shrinkage S are in such a range, it is easy to make T×S within the above-mentioned desired range.
[0051] In the optical laminate, the total thickness from the first liquid crystal orientation solidification layer to the second liquid crystal orientation solidification layer is preferably 20 μm or less, more preferably 3 μm to 10 μm. According to an embodiment of the present invention, the problem of newly discovered linear unevenness in an optical laminate comprising a very thin liquid crystal orientation solidification layer can be solved. It should be noted that if the total thickness from the first liquid crystal orientation solidification layer to the second liquid crystal orientation solidification layer is in the above-mentioned range, the total thickness from the polarizer to the second liquid crystal orientation solidification layer (excluding the actual total thickness of the optical laminate including the thickness of the adhesive for bonding to the image display panel) can be, for example, 100 μm or less, and for example, 30 μm to 80 μm.
[0052] From a practical point of view, the optical laminate has an adhesive layer (not shown) as the outermost layer on the second liquid crystal orientation solidified layer side (image display panel side), which can be attached to the image display panel. At this time, it is preferred that a release liner is temporarily bonded to the surface of the adhesive layer until the optical laminate is used. By temporarily attaching the release liner, a roll of the optical laminate can be formed while protecting the adhesive layer.
[0053] Hereinafter, the components of the optical layered body will be described in detail.
[0054] B. Polarizer
[0055] B-1. Polarizer
[0056] The polarizer 11 is typically formed of a polyvinyl alcohol (PVA) resin film containing a dichroic substance (eg, iodine). Examples of the PVA resin include polyvinyl alcohol, partially formalized polyvinyl alcohol, ethylene-vinyl alcohol copolymer, and partially saponified ethylene-vinyl acetate copolymer.
[0057] The PVA resin preferably includes an acetoacetyl-modified PVA resin. If such a structure is used, a polarizer having a desired mechanical strength can be obtained. When the PVA resin as a whole is set to 100 wt %, the blending amount of the acetoacetyl-modified PVA resin is preferably 5 wt % to 20 wt %, more preferably 8 wt % to 12 wt %. If the blending amount is such a range, a polarizer having a more excellent mechanical strength can be obtained.
[0058] The polarizer preferably contains iodide or sodium chloride (sometimes collectively referred to as halide). Examples of iodide include potassium iodide, sodium iodide, and lithium iodide. The content of halide in the polarizer is preferably 5 to 20 parts by weight, more preferably 10 to 15 parts by weight, relative to 100 parts by weight of PVA-based resin. The halide can be compounded in a coating liquid that forms a PVA-based resin layer as a precursor of the polarizer in the manufacturing method described later, and finally introduced into the polarizer. By introducing a halide into the polarizer, the orientation of the PVA molecules in the polarizer can be improved, and therefore, a polarizer with excellent optical properties (representatively, a combination of high polarization degree and high monomer transmittance) can be achieved.
[0059] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is preferably 41.0% to 46.0%, more preferably 42.0% to 45.0%. The polarization degree of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and further preferably 99.9% or more. According to an embodiment of the present invention, even if the single transmittance is in the range as described above, the polarization degree can be maintained in such a range.
[0060] The thickness of the polarizer is, for example, 12 μm or less, preferably 10 μm or less, more preferably 1 μm to 8 μm, and further preferably 3 μm to 7 μm. By combining such a thin polarizer with a liquid crystal orientation solidification layer, a significant thinning of the optical laminate can be achieved. In addition, if the thickness of the polarizer is in the above range, curling during heating can be well suppressed, and good appearance durability during heating can be obtained.
[0061] The polarizer can be produced by any appropriate method. For example, the resin film forming the polarizer may be a single-layer resin film or a laminate of two or more layers.
[0062] Specific examples of polarizers composed of a single-layer resin film include polarizers obtained by dyeing and stretching hydrophilic polymer films such as PVA films, partially formalized PVA films, and partially saponified films of ethylene-vinyl acetate copolymers using dichroic substances such as iodine and dichroic dyes, and polyene-based oriented films such as dehydrated PVA and dehydrochlorinated polyvinyl chloride. From the perspective of excellent optical properties, it is preferred to use a polarizer obtained by dyeing a PVA film with iodine and uniaxially stretching it.
[0063] The dyeing using iodine is carried out, for example, by immersing the PVA film in an iodine aqueous solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching can be carried out after the dyeing treatment or while dyeing. In addition, dyeing can also be carried out after stretching. As required, the PVA film can be subjected to swelling treatment, cross-linking treatment, cleaning treatment, drying treatment, etc. For example, by immersing the PVA film in water and washing it with water before dyeing, not only can the dirt and anti-blocking agent on the surface of the PVA film be cleaned, but also the PVA film can be swollen to prevent uneven dyeing.
[0064] As a specific example of a polarizer obtained using a laminate, there can be cited a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. The polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be made, for example, in the following manner: a PVA-based resin solution is applied to a resin substrate, dried to form a PVA-based resin layer on the resin substrate, and a laminate of the resin substrate and the PVA-based resin layer is obtained; the laminate is stretched and dyed to make the PVA-based resin layer into a polarizer. In the present embodiment, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. Stretching typically includes immersing the laminate in a boric acid aqueous solution and stretching it. Furthermore, the stretching may further include stretching the laminate in the air at a high temperature (e.g., above 95°C) before stretching in a boric acid aqueous solution as needed. In addition, in the present embodiment, it is preferred that the laminate is subjected to a drying shrinkage treatment in which the laminate is shrunk by more than 2% in the width direction by heating while being transported in the length direction. Typically, the manufacturing method of the present embodiment includes sequentially performing an air auxiliary stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment on the laminate. By introducing auxiliary stretching, the crystallinity of the PVA can be improved even when the PVA is coated on the thermoplastic resin, and high optical properties can be achieved. In addition, by simultaneously improving the orientation of the PVA in advance, when immersed in water in the subsequent dyeing process and the stretching process, problems such as the reduction and dissolution of the orientation of the PVA can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the disorder of the orientation of the polyvinyl alcohol molecules and the reduction of the orientation can be suppressed compared to the case where the PVA-based resin layer does not contain a halide. As a result, the optical properties of the polarizer obtained by the treatment process of immersing the laminate in a liquid such as a dyeing treatment and an underwater stretching treatment can be improved. Furthermore, by shrinking the laminate in the width direction using a drying shrinkage treatment, the optical properties can be improved. The obtained laminate of resin substrate / polarizer can be used directly (that is, the resin substrate can be used as a protective layer of polarizer), or can be used by laminating any appropriate protective layer according to the purpose on the peeling surface of the resin substrate peeled off from the laminate of resin substrate / polarizer, or on the surface on the opposite side of the peeling surface. The details of the manufacturing method of such a polarizer are, for example, recorded in Japanese Unexamined Patent Publication No. 2012-73580 and Japanese Patent No. 6470455. The overall records of these publications are cited in this specification as a reference.
[0065] B-2. Protective layer
[0066] The protective layers 12 and 13 are composed of any appropriate resin film. As the material constituting the resin film, representative examples include cellulose resins such as triacetyl cellulose (TAC), cycloolefin resins such as polynorbornene, (meth) acrylic resins, polyester resins such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyolefin resins such as polyethylene, and polycarbonate resins. As a representative example of (meth) acrylic resins, (meth) acrylic resins with a lactone ring structure can be listed. (Meth) acrylic resins with a lactone ring structure are, for example, recorded in Japanese Patent Publication No. 2000-230016, Japanese Patent Publication No. 2001-151814, Japanese Patent Publication No. 2002-120326, Japanese Patent Publication No. 2002-254544, and Japanese Patent Publication No. 2005-146084. These publications are cited in this specification as reference. From the viewpoint of ease of processing into a special shape, cellulose resins are preferred, and TAC is more preferred. From the viewpoint of obtaining a polarizing plate having low water vapor permeability and excellent durability, cycloolefin resins and (meth)acrylic resins are preferred.
[0067] The optical stack is typically configured on the visual recognition side of the image display device, and the protective layer 12 is typically configured on the visual recognition side. Therefore, the protective layer 12 can be surface treated as needed. As a surface treatment, for example, hard coating, anti-reflection treatment, anti-adhesion treatment, and anti-glare treatment can be listed. And / or, the protective layer 12 can also be implemented as needed to improve the processing of visual recognition when visually recognized across polarized sunglasses (representatively, giving (elliptical) circular polarization function, giving ultra-high phase difference). By implementing such a treatment, even in the case of visually recognizing the display screen across polarized lenses such as polarized sunglasses, excellent visual recognition can be achieved. Therefore, the optical stack can also be suitably applied to image display devices that can be used outdoors.
[0068] In one embodiment, the protective layer 13 is preferably optically isotropic. In this specification, the term "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm and the thickness direction retardation Rth(550) is -10 nm to +10 nm.
[0069] The thickness of each of the protective layers 12 and 13 is preferably 10 to 80 μm, more preferably 12 to 40 μm, and further preferably 15 to 35 μm. When the protective layer 12 is surface treated, the thickness of the protective layer 12 includes the thickness of the surface treated layer.
[0070] C. Phase difference layer
[0071] As described above, the phase difference layer 20 includes the first liquid crystal orientation solidification layer 21 and the second liquid crystal orientation solidification layer 22 in order from the polarizing plate side. Furthermore, as described above, the phase difference layer 20 as a whole (as a laminate of the first liquid crystal orientation solidification layer 21 and the second liquid crystal orientation solidification layer 22) has a circular polarization function or an elliptical polarization function, and has a relationship of Re(450)<Re(550)<Re(650). Regarding the description of the phase difference layer in this item, when it is simply referred to as a "phase difference layer", it means that it is described as a whole phase difference layer, and when it is simply referred to as a "liquid crystal orientation solidification layer", it means that the first liquid crystal orientation solidification layer and the second liquid crystal orientation solidification layer are collectively described.
[0072] The Re(550) of the phase difference layer 20 is preferably 100 nm to 200 nm, more preferably 110 nm to 180 nm, further preferably 120 nm to 170 nm, and particularly preferably 130 nm to 150 nm. When the Re(550) of the phase difference layer is within such a range, the phase difference layer can be combined with a polarizer to exhibit a good circular polarization function or an elliptical polarization function.
[0073] The phase difference layer 20 has a relationship of Re(450)<Re(550)<Re(650). That is, the phase difference layer 20 preferably shows a wavelength dependence of reverse dispersion in which the phase difference value increases with the wavelength of the measured light. If it is such a structure, a good anti-reflection function can be achieved in a very wide wavelength range. Re(450) / Re(550) is, for example, greater than 0.5 and less than 1.0, preferably 0.7 to 0.95, more preferably 0.75 to 0.92, and further preferably 0.8 to 0.9. Re(650) / Re(550) is preferably greater than 1.0 and less than 1.15, more preferably 1.03 to 1.1.
[0074] In one embodiment, the Nz coefficient of the phase difference layer 20 can be, for example, 0.30 to 0.70 as described above. Therefore, the phase difference layer 20 shows a refractive index characteristic of nx>nz>ny. According to such a structure, reflection in the oblique direction can be well prevented, and a wide viewing angle of the anti-reflection function can be achieved. The Nz coefficient is preferably 0.35 to 0.65, more preferably 0.40 to 0.60, and further preferably 0.45 to 0.55.
[0075] As the liquid crystal compound used in the liquid crystal orientation solidification layer, for example, liquid crystal polymers and liquid crystal monomers can be listed. The liquid crystal compound is preferably capable of polymerization (i.e., liquid crystal monomer). If the liquid crystal compound is capable of polymerization, then by polymerizing after the liquid crystal compound is oriented, the orientation state of the liquid crystal compound can be fixed. Here, the polymer formed by polymerization is non-liquid crystal. Therefore, the formed liquid crystal orientation solidification layer will not undergo a change in temperature, such as that of a liquid crystal compound, resulting in a transition to a liquid crystal phase, a glass phase, or a crystalline phase. As a result, the liquid crystal orientation solidification layer becomes a phase difference layer having excellent stability that is not affected by temperature changes.
[0076] In one embodiment, the liquid crystal orientation solidification layer can be formed using a composition comprising a liquid crystal compound (polymerizable liquid crystal compound, i.e., liquid crystal monomer) that can be polymerized. In this specification, the polymerizable liquid crystal compound contained in the composition refers to a compound having a polymerizable group and having liquid crystal properties. The polymerizable group refers to a group participating in the polymerization reaction, preferably a photopolymerizable group. Here, the photopolymerizable group refers to a group that can participate in the polymerization reaction by an active free radical, acid, etc. produced by a photopolymerization initiator. As a liquid crystal monomer, for example, the polymerizable mesogen compounds described in Japanese Patent Application No. 2002-533742 (WO00 / 37585), EP 358208 (US 5211877), EP 66137 (US 4388453), WO 93 / 22397, EP 0261712, DE 19504224, DE 4408171 and GB 2280445, etc. can be used. Specific examples of such polymerizable mesogen compounds include LC 242 (trade name) from BASF, E7 (trade name) from Merck, and LC-Sillicon-CC 3767 (trade name) from Wacker-Chem.
[0077] The liquid crystal compound may be thermotropic or lyotropic in its liquid crystal properties. In addition, the liquid crystal phase may be a nematic liquid crystal or a smectic liquid crystal. From the perspective of ease of manufacture, a nematic liquid crystal having a thermotropic liquid crystal property is preferred.
[0078] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on its type. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.
[0079] The birefringence Δn of the liquid crystal orientation solidified layer is preferably 0.06 or more, more preferably 0.08 or more, further preferably 0.09 or more, and particularly preferably 0.10 or more. The upper limit of Δn can be, for example, 0.13, and can be, for example, 0.12. If Δn is in such a range, the desired in-plane phase difference can be achieved with a very thin thickness. As a result, the liquid crystal orientation solidified layer and the optical laminate can be further thinned, which can ultimately contribute to the significant thinning of the image display device.
[0080] The liquid crystal orientation solidified layer can show a reverse dispersion wavelength characteristic in which the phase difference value increases according to the wavelength of the measuring light, a positive wavelength dispersion characteristic in which the phase difference value decreases according to the wavelength of the measuring light, or a flat wavelength dispersion characteristic in which the phase difference value hardly changes with the wavelength of the measuring light.
[0081] The first liquid crystal orientation solidification layer 21 can function as a λ / 2 plate, and the second liquid crystal orientation solidification layer 22 can function as a λ / 4 plate. Specifically, the Re(550) of the first liquid crystal orientation solidification layer is preferably 150nm to 300nm, more preferably 200nm to 270nm, and further preferably 220nm to 260nm; the Re(550) of the second liquid crystal orientation solidification layer is preferably 100nm to 200nm, more preferably 110nm to 160nm, and further preferably 120nm to 140nm. The thickness of the first liquid crystal orientation solidification layer can be adjusted in a manner to obtain the desired in-plane phase difference of the λ / 2 plate. In one embodiment, the thickness of the first liquid crystal orientation solidification layer can be, for example, 2.0μm to 4.0μm. In another embodiment, the thickness of the first liquid crystal orientation solidification layer is preferably 1.7μm or less, more preferably 1.6μm or less, and further preferably 1.5μm or less. In this case, the thickness of the first liquid crystal orientation solidification layer can be, for example, 1.3μm or more. Like this, according to an embodiment of the present invention, the thickness of the first liquid crystal orientation solidification layer can be made thinner than before, and linear unevenness can be suppressed. The thickness of the second liquid crystal orientation solidification layer can be adjusted in a manner to obtain the desired in-plane phase difference of the λ / 4 plate. Specifically, its thickness can be, for example, 0.8μm to 2.5μm. The angle between the slow axis of the first liquid crystal orientation solidification layer and the transmission axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and further preferably 14° to 16°; the angle between the slow axis of the second liquid crystal orientation solidification layer and the transmission axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and further preferably 74° to 76°. It should be noted that the configuration order of the first liquid crystal orientation solidification layer and the second liquid crystal orientation solidification layer can be opposite, and the angle between the slow axis of the first liquid crystal orientation solidification layer and the transmission axis of the polarizer and the angle between the slow axis of the second liquid crystal orientation solidification layer and the transmission axis of the polarizer can also be opposite.
[0082] The refractive index of the liquid crystal alignment cured layer may vary depending on the composition forming the liquid crystal alignment cured layer (substantially the type of liquid crystal compound, the type, amount, combination, blending amount, etc. of additives). LC1 The refractive index n of the second liquid crystal alignment curing layer LC2 They may be the same or different from each other (the refractive index n of the first liquid crystal alignment solidification layer may be LC1 The refractive index n of the second liquid crystal alignment solidification layer can also be larger. LC2 The refractive index n of the first liquid crystal alignment solidification layer is greater. LC1 The refractive index n of the second liquid crystal alignment solidified layer is preferably 1.55 to 1.75, and more preferably 1.60 to 1.70. LC2 The refractive index n of the first liquid crystal alignment solidified layer is preferably 1.45 to 1.65, and more preferably 1.50 to 1.60. LC1 The refractive index n of the second liquid crystal alignment curing layer LC2 The refractive index n of the first liquid crystal alignment solidification layer may be the opposite. LC1 The refractive index n of the second liquid crystal alignment curing layer LC2 The absolute value of the difference can be, for example, 0.00 to 0.20. The refractive index of the liquid crystal orientation solidification layer is typically based on the composition of the liquid crystal orientation solidification layer in order to obtain the desired optical properties. As a result, linear unevenness sometimes occurs. In this case, according to an embodiment of the present invention, the linear unevenness can be suppressed by making the thickness deviation in a specified area of the adhesive layer less than 0.16 μm, and / or making the thickness T of the adhesive layer and the curing shrinkage S of the adhesive constituting the adhesive layer satisfy the relationship of T×S≤17.
[0083] It is also possible to introduce a side chain type thermotropic liquid crystal polymer into the first liquid crystal orientation solidification layer and / or the second liquid crystal orientation solidification layer (essentially the liquid crystal composition forming them). By introducing a side chain type thermotropic liquid crystal polymer, the effect of vertically oriented liquid crystal monomers (homeotropic orientation) can be produced. As a result, the nz of the first liquid crystal orientation solidification layer and / or the second liquid crystal orientation solidification layer can be increased, and as a result, the Nz coefficient of the first liquid crystal orientation solidification layer and / or the second liquid crystal orientation solidification layer can be within the above-mentioned desired range. Finally, the Nz coefficient of the phase difference layer can be within the above-mentioned desired range without setting the positive C plate described later.
[0084] As the side chain type thermotropic liquid crystal polymer, a copolymer having a monomer unit containing a thermotropic liquid crystal segment side chain and a monomer unit containing a non-liquid crystal segment side chain is typically used. When the polymer has a thermotropic liquid crystal segment in the side chain, the side chain type liquid crystal polymer can be oriented when the liquid crystal composition is heated to a predetermined temperature. In addition, when the side chain type polymer has a non-liquid crystal segment in the side chain, the non-liquid crystal segment interacts with the photopolymerizable liquid crystal monomer, which can produce an effect of vertically aligning the photopolymerizable liquid crystal monomer.
[0085] As the side chain type thermotropic liquid crystal polymer, a copolymer having a liquid crystal monomer unit represented by the general formula (I) and a non-liquid crystal monomer unit represented by the general formula (II) is preferably used.
[0086]
[0087] In formula (I), R 1 is a hydrogen atom or a methyl group, R 2 is a cyano group, a fluoro group, an alkyl group having 1 to 6 carbon atoms, or an alkoxy group having 1 to 6 carbon atoms, and X 1 For -CO 2 - or -OCO-. a is an integer of 1 to 6, and b and c are 1 or 2 each independently.
[0088] In formula (II), R 3 is a hydrogen atom or a methyl group, R 4 It is an alkyl group having 7 to 22 carbon atoms, a fluoroalkyl group having 1 to 22 carbon atoms, or a group represented by the following general formula (III).
[0089]
[0090] In formula (III), R 5 is an alkyl group having 1 to 5 carbon atoms, and d is an integer of 1 to 6.
[0091] The ratio of the liquid crystal monomer unit to the non-liquid crystal monomer unit in the side chain type liquid crystal polymer can be appropriately set according to the purpose. Relative to the total of the liquid crystal monomer unit and the non-liquid crystal monomer unit, the ratio (molar ratio) of the non-liquid crystal monomer is preferably 0.05 to 0.8, more preferably 0.1 to 0.6, and further preferably 0.15 to 0.5. If it is such a structure, a liquid crystal orientation solidified layer showing the desired refractive index characteristics (Nz coefficient) can be obtained.
[0092] The ratio of the liquid crystal monomer to the side chain liquid crystal polymer in the liquid crystal composition can be appropriately set according to the purpose. When the content of the side chain liquid crystal polymer is high, there is a tendency for the Nz coefficient to become smaller; when the content of the liquid crystal monomer is high, there is a tendency for the Nz coefficient to become larger. Relative to the content of the side chain liquid crystal polymer, the content of the liquid crystal monomer is preferably 1.2 times to 20 times, more preferably 1.3 times to 10 times, further preferably 1.4 times to 9 times, and particularly preferably 1.5 times to 8 times. If it is such a structure, a liquid crystal orientation solidified layer showing the desired refractive index characteristics (Nz coefficient) can be obtained.
[0093] Details of the side chain type liquid crystal polymer and the method for forming a liquid crystal alignment solidified layer having an Nz coefficient of less than 1.0 are described in Japanese Patent No. 6769921. The description of this patent is incorporated herein by reference.
[0094] The phase difference layer 20 may further include a positive C plate. The refractive index characteristics of the positive C plate show a relationship of nz>nx=ny. The phase difference Rth(550) in the thickness direction of the positive C plate is preferably -20nm~-300nm, more preferably -30nm~-250nm, further preferably -40nm~-200nm, and particularly preferably -50nm~-150nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane phase difference Re(550) of the positive C plate can be less than 10nm.
[0095] The positive C plate can be formed, for example, using a composition containing the above-mentioned side chain type liquid crystal polymer. As a specific example of the method for forming the positive C plate, there can be cited the method described in
[0020] to
[0028] of Japanese Patent Publication No. 2002-333642. At this time, the thickness of the positive C plate is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and further preferably 0.5 μm to 5 μm.
[0096] D. Adhesive layer
[0097] The adhesive layer 30 may have any appropriate configuration as long as the desired thickness deviation and / or the desired T×S are achieved. The adhesive layer 30 may be typically composed of an active energy ray-curable adhesive as described above.
[0098] As the active energy ray-curable adhesive, any appropriate active energy ray-curable adhesive can be used. As the active energy ray-curable adhesive, for example, ultraviolet curable adhesives and electron beam curable adhesives can be listed. In addition, from the viewpoint of the curing mechanism, as active energy ray-curable adhesives, for example, free radical curing, cation curing, anion curing, and a mixture of free radical curing and cation curing can be listed. Representatively, a free radical-curable ultraviolet curing adhesive can be used. This is because it has excellent versatility and easy adjustment of characteristics (structure).
[0099] Active energy ray curing adhesives typically contain monofunctional components, multifunctional components (curing components) and photopolymerization initiators. Monofunctional components and multifunctional components are each typically free radical polymerizable compounds. As preferred monofunctional components, for example, higher alkyl esters of (meth) acrylic acid and modified bodies thereof can be cited. Specifically, isostearyl acrylate, lauryl acrylate, acryloyl morpholine, unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone, etc. can be cited. By using such a monofunctional component with a large molecular weight per functional group, an adhesive with a small curing shrinkage can be obtained. As a result, an adhesive layer with a small thickness deviation can be obtained. As preferred multifunctional components, for example, monomers and / or oligomers having functional groups such as more than two (meth) acrylate groups and (meth) acrylamide groups can be cited. Specifically, polyethylene glycol diacrylate, trimethylolpropane triacrylate, and glycerol triacrylate can be cited. As specific examples of monofunctional components other than the above, tripropylene glycol diacrylate, 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, phenoxydiethylene glycol acrylate, cyclic trimethylolpropane formal acrylate, dioxanediol diacrylate, EO modified diglycerol tetraacrylate, γ-butyrolactone acrylate, N-methylpyrrolidone, hydroxyethyl acrylamide, N-hydroxymethyl acrylamide, N-methoxymethyl acrylamide, N-ethoxymethyl acrylamide, 9-vinyl carbazole, 4-vinylphenyl boronic acid, fluorene acrylate. In one embodiment, the monofunctional component or the multifunctional component has a ring structure. Specifically, acryloyl morpholine, γ-butyrolactone acrylate, unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone, N-methylpyrrolidone, 9-vinyl carbazole, fluorene acrylate can be listed. The free volume of the compound having a ring structure is small (high density), so by using such a compound, an adhesive with a small curing shrinkage can be obtained. As a result, an adhesive layer with a small thickness deviation can be obtained. The monofunctional component or the multifunctional component can be used only one, or two or more can be used in combination.
[0100] The active energy ray-curable adhesive may further contain a cationic polymerizable compound as needed. The cationic polymerizable compound may be monofunctional or polyfunctional. As monofunctional cationic polymerizable compounds, for example, p-tert-butylphenyl glycidyl ether and 3-ethyl-3-[(2-ethylhexyl)oxy]oxetane may be listed. As polyfunctional cationic polymerizable compounds, for example, 3-ethyl-3-{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane may be listed. As cationic polymerizable compounds, silane coupling agents may also be used. As silane coupling agents, for example, 3-glycidoxypropyltrimethoxysilane may be listed.
[0101] The active energy ray curing adhesive can further contain an acrylic oligomer as required. The molecular weight of the acrylic oligomer can be appropriately set according to the purpose. By using an acrylic oligomer that does not form further bonds, an adhesive with a small curing shrinkage can be obtained. As a result, an adhesive layer with a small thickness deviation can be obtained.
[0102] The active energy ray-curable adhesive may further contain a photopolymerization initiator as necessary. Examples of the photopolymerization initiator include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 1-hydroxycyclohexyl phenyl ketone, and diethylthioxanthone.
[0103] The active energy ray-curable adhesive may further contain a plasticizer (for example, an oligomer component), a crosslinking agent, a diluent, etc., depending on the purpose. In addition, commercially available products can be used for the above-mentioned components.
[0104] The smaller the absolute value of the difference between the refractive index of the active energy ray-curable adhesive and the refractive index of the adjacent layer (particularly the first liquid crystal alignment cured layer) is, the more preferable it is.
[0105] The details of the active energy ray-curable adhesive are described in, for example, Japanese Patent Application Laid-Open No. 2018-017996. The description of the publication is incorporated herein by reference.
[0106] E. Interlayer bonding layer
[0107] E-1. Overview
[0108] As described above, the interlayer adhesive layer (not shown) is an adhesive layer for laminating the first liquid crystal alignment fixed layer 21 and the second liquid crystal alignment fixed layer 22. The interlayer adhesive layer may be composed of a binder or an adhesive.
[0109] In one embodiment, the refractive index n of the first liquid crystal alignment solidification layer is LC1 , the refractive index n of the second liquid crystal alignment curing layer LC2 , and the refractive index n of the interlayer adhesive layerAD , and the thickness T of the interlayer adhesive layer AD and thickness deviation TV AD The following formula (1) is satisfied. It should be noted that the left side of formula (1) is sometimes referred to as the display unevenness parameter. In addition, the "refractive index" of the liquid crystal orientation solidification layer in this specification refers to the refractive index in the transmission axis direction of the polarizer unless otherwise specified. The adhesive layer is substantially optically isotropic, so the refractive index n AD It is also isotropic.
[0110] |{(n LC1 +n LC2 ) / 2-n AD}|×(TV AD / T AD )×1000≤3.0 (1)
[0111] The display unevenness parameter is preferably 2.5 or less, more preferably 2.0 or less, further preferably 1.8 or less, particularly preferably 1.2 or less, and particularly preferably 0.7 or less. The smaller the display unevenness parameter (absolute value), the more preferred, and may be 0.0, for example.
[0112] Regardless of whether the interlayer adhesive layer is an adhesive layer or a pressure-sensitive adhesive layer, the refractive index n of the interlayer adhesive layer is AD For example, it may be 1.45 or more, or 1.50 or more, or 1.52 or more. The refractive index n of the interlayer adhesive layer is AD It is preferably 1.54 or more, more preferably 1.55 or more, further preferably 1.57 or more, and particularly preferably 1.60 or more. AD For example, it may be 1.63 or less.
[0113] When the interlayer adhesive layer is an adhesive layer, the thickness T of the interlayer adhesive layer is AD For example, it is 3 μm or more, preferably 4 μm or more, more preferably 5 μm or more, further preferably 10 μm or more, and particularly preferably 15 μm or more. AD For example, it may be 30 μm or less. When the interlayer adhesive layer is an adhesive layer, the thickness T of the interlayer adhesive layer is AD The thickness deviation TV of the interlayer adhesive layer is preferably 0.5 μm to 2.0 μm, and more preferably 0.8 μm to 1.2 μm. AD It is preferably 0.20 μm or less, more preferably 0.18 μm or less, and even more preferably 0.16 μm or less. AD For example, it may be 0.03 μm or more.
[0114] Hereinafter, the binder and the adhesive constituting the interlayer adhesive layer will be described respectively.
[0115] E-2. Adhesive
[0116] As adhesive, as long as the above characteristics are met, any appropriate composition can be adopted. As the specific example of adhesive, acrylic adhesive, rubber adhesive, silicone adhesive, polyester adhesive, urethane adhesive, epoxy adhesive, and polyether adhesive can be listed. By adjusting the type, quantity, combination and blending ratio of the monomers of the base polymer forming the adhesive, as well as the blending amount, reaction temperature, reaction time, etc. of the crosslinking agent, an adhesive with the desired characteristics corresponding to the target can be prepared. The base polymer of the adhesive can be used alone or in combination with more than two kinds. From the viewpoints of transparency, processability and durability, acrylic adhesive (acrylic adhesive composition) is preferably used. Acrylic adhesive composition is representatively comprised of (methyl) acrylic polymers as main components of the base polymer. In the solid component of the adhesive composition, (methyl) acrylic polymers can be included in the adhesive composition with, for example, more than 50% by weight, preferably more than 70% by weight, more preferably more than 90% by weight. It should be noted that (methyl) acrylate refers to acrylate and / or methacrylate.
[0117] The (meth)acrylic polymer preferably contains an aromatic ring-containing monomer (m1) as a monomer component. As the monomer (m1), a compound containing at least one aromatic ring and at least one ethylenically unsaturated group in one molecule can be used. As the monomer (m1), such a compound can be used alone or in combination of two or more. The aromatic ring and the ethylenically unsaturated group can be directly bonded or bonded via a connecting group.
[0118] As the ethylenically unsaturated group, for example, (meth)acryloyl, vinyl, and (meth)allyl can be cited. From the viewpoint of polymerization reactivity, (meth)acryloyl is preferred, and from the viewpoint of flexibility and adhesiveness, acryloyl is more preferred. From the viewpoint of suppressing the decrease in the flexibility of the adhesive, as the monomer (m1), a compound having 1 ethylenically unsaturated group contained in one molecule (i.e., a monofunctional monomer) is preferably used.
[0119] The number of aromatic rings contained in one molecule of the compound used as the monomer (m1) may be 1 or more than 2. The upper limit of the number of aromatic rings contained in the monomer (m1) is not particularly limited, and may be, for example, 16 or less. In some embodiments, from the perspective of the ease of preparation of the (meth)acrylic polymer and the transparency of the adhesive, the number of aromatic rings may be, for example, 12 or less, preferably 8 or less, more preferably 6 or less, 5 or less, 4 or less, 3 or less, or 2 or less.
[0120] The aromatic ring possessed by the compound used as monomer (m1) can be, for example, a benzene ring (which can be a benzene ring constituting a part of a biphenyl structure or a fluorene structure), a naphthalene ring, an indene ring, an azulene ring, an anthracene ring, a phenanthrene ring, and other carbon rings; it can also be, for example, a pyridine ring, a pyrimidine ring, a pyridazine ring, a pyrazine ring, a triazine ring, a pyrrole ring, a pyrazole ring, an imidazole ring, a triazole ring, an oxazole ring, an isoxazole ring, a thiazole ring, a thiophene ring, and other heterocyclic rings. The heteroatoms included as ring-forming atoms in the above-mentioned heterocyclic rings can be, for example, one or more of the group consisting of nitrogen, sulfur, and oxygen. In some embodiments, the heteroatoms constituting the heterocyclic ring can be one or both of nitrogen and sulfur. Monomer (m1) can also have a structure formed by condensing one or more carbon rings with one or more heterocyclic rings, such as a dinaphthothiophene structure.
[0121] Examples of compounds that can be preferably used as monomer (m1) include aromatic ring-containing (meth)acrylates and aromatic ring-containing vinyl compounds. Aromatic ring-containing (meth)acrylates and aromatic ring-containing vinyl compounds can be used alone or in combination of two or more. One or two or more aromatic ring-containing (meth)acrylates can be used in combination with one or two or more aromatic ring-containing vinyl compounds.
[0122] The content of the monomer (m1) in the monomer component constituting the (meth) acrylic polymer can be set, for example, in a manner that can achieve an adhesive layer that takes into account the desired refractive index and adhesion properties (such as peel strength, flexibility, etc.) and / or optical properties (such as total light transmittance, haze value, etc.). In some embodiments, the content of the monomer (m1) in the monomer component can be, for example, 30% by weight or more, preferably 50% by weight or more, 60% by weight or more, or 70% by weight or more. From the viewpoint of easily obtaining a higher refractive index, in some embodiments, the content of the monomer (m1) can, for example, exceed 70% by weight, can be 75% by weight or more, can be 80% by weight or more, can be 85% by weight or more, can be 90% by weight or more, or can be 95% by weight or more. The upper limit of the content of the monomer (m1) in the monomer component is 100% by weight. From the viewpoint of balancing the high refractive index with the adhesive properties and / or optical properties, it is advantageous for the content of the above-mentioned monomer (m1) to be less than 100 wt %, for example, preferably about 99 wt % or less, more preferably 98 wt % or less, 97 wt % or less, or 96 wt % or less. In some embodiments, the content of the monomer (m1) may be 93 wt % or less, 90 wt % or less, 80 wt % or less, or 75 wt % or less. In some embodiments where adhesive properties and / or optical properties are given more importance, the content of the monomer (m1) in the monomer component may be 70 wt % or less, 60 wt % or less, or 45 wt % or less.
[0123] In some embodiments, as a monomer (m1), from the aspect of easily obtaining a high refractive index effect, a monomer having two or more aromatic rings (preferably a carbon ring) in one molecule can be preferably used. As an example of a monomer having two or more aromatic rings in one molecule (hereinafter, also referred to as a "monomer containing multiple aromatic rings"), there can be listed a monomer having a structure in which two or more non-condensed aromatic rings are bonded via a connecting group, a monomer having a structure in which two or more non-condensed aromatic rings are directly (i.e., not via other atoms) chemically bonded, a monomer having a condensed aromatic ring structure, a monomer having a fluorene structure, a monomer having a dinaphthothiophene structure, a monomer having a dibenzothiophene structure, etc. A monomer containing multiple aromatic rings can be used alone or in combination of two or more.
[0124] As at least a part of the monomer (m1), a high refractive index monomer can be preferably used. Here, "high refractive index monomer" refers to a monomer whose refractive index is, for example, about 1.510 or more, preferably about 1.530 or more, and more preferably about 1.550 or more. There is no particular limit to the upper limit of the refractive index of the high refractive index monomer. From the perspective of the ease of preparation of the adhesive composition and the ease of flexibility suitable as an adhesive, it can be, for example, 3.000 or less, 2.500 or less, 2.000 or less, 1.900 or less, 1.800 or less, or 1.700 or less. The high refractive index monomer can be used alone or in combination of two or more.
[0125] The refractive index of the monomer can be measured, for example, using an Abbe refractometer at a measurement wavelength of 589 nm and a measurement temperature of 25° C. As the Abbe refractometer, a model "DR-M4" manufactured by ATAGO or an equivalent thereof can be used. When a nominal value of the refractive index at 25° C. is provided by a manufacturer or the like, the nominal value can be used.
[0126] As the high refractive index monomer, a monomer having a corresponding refractive index can be appropriately adopted from the compounds included in the concept of the aromatic ring-containing monomer (m1) (for example, the compounds and compound groups exemplified above). Specific examples include m-phenoxybenzyl acrylate (refractive index: 1.566, Tg of homopolymer: -35°C), 1-naphthylmethyl acrylate (refractive index: 1.595, Tg of homopolymer: 31°C), ethoxylated o-phenylphenol acrylate (number of repetitions of oxyethylene units: 1, refractive index: 1.578), benzyl acrylate (refractive index (nD20): 1.519, Tg of homopolymer: 6°C), phenoxyethyl acrylate (refractive index (nD20): 1.517, Tg of homopolymer: 2°C), phenoxydiethylene glycol acrylate (refractive index: 1.510, Tg of homopolymer: 31°C), and the like. Polymer Tg: -35 ° C), 6-acryloxymethyl dinaphthothiophene (6MDNTA, refractive index: 1.75), 6-methacryloxymethyl dinaphthothiophene (6MDNTMA, refractive index: 1.726), 5-acryloxyethyl dinaphthothiophene (5EDNTA, refractive index: 1.786), 6-acryloxyethyl dinaphthothiophene (6EDNTA, refractive index: 1.722), 6-vinyl dinaphthothiophene (6VDNT, refractive index: 1.802), 5-vinyl dinaphthothiophene (abbreviation: 5VDNT, refractive index: 1.793).
[0127] The content of the high refractive index monomer (i.e., an aromatic ring-containing monomer having a refractive index of about 1.510 or more, preferably about 1.530 or more, and more preferably about 1.550 or more) in the monomer (m1) is not particularly limited, and may be, for example, 5% by weight or more, 25% by weight or more, 35% by weight or more, or 40% by weight or more. In some embodiments, from the viewpoint of easily obtaining a higher refractive index, the content of the high refractive index monomer in the monomer (m1) may be, for example, 50% by weight or more, preferably 70% by weight or more, 85% by weight or more, 90% by weight or more, or 95% by weight or more. Substantially 100% by weight of the monomer (m1) may be a high refractive index monomer. In addition, in some embodiments, for example, from the viewpoint of balancing the high refractive index with adhesive properties and / or optical properties, the content of the high refractive index monomer in the monomer (m1) may be less than 100% by weight, may be less than 98% by weight, may be less than 90% by weight, may be less than 80% by weight, or may be less than 65% by weight. In some embodiments, considering the adhesive properties and / or optical properties, the content of the high refractive index monomer in the monomer (m1) may be 70 wt % or less, 50 wt % or less, 25 wt % or less, 15 wt % or less, or 10 wt % or less. The embodiments of the present invention may be implemented even if the content of the high refractive index monomer in the monomer (m1) is less than 5 wt %. The high refractive index monomer may not be used.
[0128] The (meth)acrylic polymer may also contain a monomer (comonomer) copolymerizable with the aromatic ring-containing monomer (m1) as a monomer component. Examples of the comonomer include aliphatic alkyl (meth)acrylates, alicyclic alkyl (meth)acrylates, carboxyl-containing monomers, hydroxyl-containing monomers, and amide-containing monomers. The type, quantity, combination, and content of the comonomer in the monomer component may be appropriately set according to the purpose.
[0129] Acrylic adhesive (acrylic adhesive composition) can contain a refractive index enhancer according to the purpose. In this specification, a refractive index enhancer refers to a material that can increase the refractive index of the adhesive layer by its use. As a refractive index enhancer, a material having a refractive index higher than the refractive index of the adhesive layer containing the refractive index enhancer can be preferably used. In addition, as a refractive index enhancer, a material having a refractive index higher than the base polymer (such as an acrylic polymer) of the adhesive layer containing the refractive index enhancer can be preferably used. By appropriately using a refractive index enhancer, a higher refractive index and practical adhesive performance can be appropriately taken into account. In some embodiments, the refractive index enhancer is preferably an organic material. The organic material used as a refractive index enhancer can be a polymer or a non-polymer. In addition, it can have a polymerizable functional group or not. The refractive index enhancer can be used alone or in combination of two or more.
[0130] Relative to 100 parts by weight of base polymer, the amount of refractive index enhancer (their total amount when using multiple refractive index enhancers) can be appropriately set according to the purpose. From the viewpoint of the high refractive index of the adhesive, relative to 100 parts by weight of the base polymer, the amount of the refractive index enhancer can be set to, for example, more than 1 part by weight, and it is advantageous to be set to more than 3 parts by weight, preferably more than 5 parts by weight, more than 7 parts by weight, more than 10 parts by weight, more than 15 parts by weight, or more than 20 parts by weight. In addition, in some embodiments, relative to 100 parts by weight of the base polymer, the amount of the refractive index enhancer can be set to, for example, less than 80 parts by weight, from the viewpoint of well-balanced high refractive index of the adhesive and the reduction and suppression of the adhesive properties and optical properties, it is advantageous to be set to less than 60 parts by weight, preferably less than 45 parts by weight. In some embodiments where adhesive properties and optical properties are more important, the amount of the refractive index enhancer can be, for example, 30 parts by weight or less, 20 parts by weight or less, 15 parts by weight or less, 10 parts by weight or less, 5 parts by weight or less, or 3 parts by weight or less relative to 100 parts by weight of the base polymer. The embodiments of the present invention can also be implemented in the adhesive layer in which the amount of the refractive index enhancer relative to 100 parts by weight of the base polymer is less than 1 part by weight, or in which substantially no refractive index enhancer is used. Here, substantially no use means at least not intentionally used.
[0131] (Additives (H RO ))
[0132] In some embodiments, as the refractive index enhancer, an organic material having a higher refractive index than the base polymer may be preferably used. Hereinafter, such an organic material is sometimes referred to as an "additive (H RO )". Here, "H RO" indicates an organic material with a high refractive index. Additives (H RO ) may be used alone or in combination of two or more.
[0133] As an additive (H RO ) can be selected from organic materials, such as organic compounds having aromatic rings and organic compounds having heterocyclic rings (which may be aromatic rings or non-aromatic heterocyclic rings). RO The aromatic ring possessed by the organic compound having an aromatic ring (hereinafter also referred to as "aromatic ring-containing compound") can be selected from the same aromatic rings as the aromatic ring possessed by the compound used as the monomer (m1).
[0134] As an additive (H RO ) include: benzyl acrylate, m-phenoxybenzyl acrylate, 2-(o-phenylphenoxy)ethyl acrylate, phenoxyethyl acrylate, phenoxydiethylene glycol acrylate, phenoxypolyethylene glycol acrylate, 2-hydroxy-3-phenoxypropyl acrylate, aromatic ring-containing monomers such as the monomers having a fluorene structure as described above, monomers having a dinaphthothiophene structure, monomers having a dibenzothiophene structure, and aromatic ring-containing compounds not having an ethylenically unsaturated group such as 3-phenoxybenzyl alcohol, dinaphthothiophene and its derivatives (for example, compounds having a structure in which one or more substituents selected from a hydroxyl group, a methanol group, a diethanol group, a glycidyl group, etc. are bonded to the dinaphthothiophene ring).
[0135] The acrylic adhesive composition may preferably contain a silane coupling agent and / or a crosslinking agent. As the silane coupling agent, for example, epoxy-containing silane coupling agents may be cited. As the crosslinking agent, for example, isocyanate-based crosslinking agents and peroxide-based crosslinking agents may be cited. Furthermore, the acrylic adhesive composition may also contain additives. As specific examples of additives, powders such as antioxidants, conductive agents, colorants, pigments, dyes, surfactants, plasticizers, tackifiers, surface lubricants, leveling agents, softeners, anti-aging agents, light stabilizers, ultraviolet light absorbers, inhibitors, inorganic or organic fillers, metal powders, granular, foil-like objects may be cited. In addition, within the controllable range, a redox system with a reducing agent added may also be used. The type, quantity, combination, content, etc. of the silane coupling agent, crosslinking agent and / or additive may be appropriately set according to the purpose.
[0136] E-3. Adhesive
[0137] The adhesive (adhesive composition) may typically contain: (meth)acrylate containing an aromatic ring skeleton and metal oxide particles. These are briefly described below. It should be noted that other components that may be included in the adhesive (such as curing components, adhesives) may adopt known structures, so specific descriptions are omitted.
[0138] By containing a (meth)acrylate having an aromatic ring skeleton in the adhesive composition, an adhesive layer having a desired refractive index can be formed in an embodiment of the present invention. As a (meth)acrylate having an aromatic ring skeleton, it is preferred to use a (meth)acrylate containing at least one selected from the group consisting of a (meth)acrylate having a polycyclic aromatic ring skeleton and a (meth)acrylate having more than two aromatic rings. As such a (meth)acrylate, for example, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxydiethylene glycol acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 1-naphthyl (meth)acrylate, phenoxybenzyl (meth)acrylate, ethylene oxide-modified o-phenylphenol (meth)acrylate, 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene and (meth)acrylic acid reaction product. Among them, phenoxybenzyl (meth)acrylate and phenoxyethyl (meth)acrylate are more preferably used, and phenoxybenzyl (meth)acrylate is particularly preferably used. When the total amount of the adhesive composition is 100% by mass, the amount of the (meth)acrylate having an aromatic ring skeleton is preferably 20% by mass to 90% by mass, and more preferably 30% by mass to 80% by mass.
[0139] As metal oxide particles, for example, silicon oxide, zirconium oxide, titanium oxide, zinc oxide, antimony pentoxide, tin oxide, aluminum oxide, indium oxide, indium tin oxide, iron oxide, cerium oxide, yttrium oxide, manganese oxide, holmium oxide, copper oxide, bismuth oxide, cobalt oxide, cobalt tetraoxide, iron tetraoxide, magnesium oxide, lanthanum oxide, praseodymium oxide, neodymium oxide, samarium oxide, europium oxide, gadolinium oxide, terbium oxide, dysprosium oxide, erbium oxide, thulium oxide, ytterbium oxide, lutetium oxide, scandium oxide, tantalum pentoxide, niobium pentoxide, iridium oxide, rhodium oxide, ruthenium oxide and composite oxides formed by combining them can be listed. Among them, zirconium oxide and titanium oxide are preferred, and zirconium oxide is particularly preferred. It should be noted that the metal oxide particles can be composed only of the metal oxides listed above, or can also contain other components, but as a component in the particles, it is preferred that the metal oxide accounts for the largest weight. The metal oxide particles may be in any shape such as spherical, ellipsoidal, cubic, rectangular or pyramidal. The metal oxide particles may be those surface-treated by any appropriate method.
[0140] From the viewpoint of improving the stability of the metal oxide particles in the adhesive composition and the refractive index of the adhesive layer, the average particle size of the metal oxide particles is preferably 1 nm to 150 nm, and more preferably 1 nm to 50 nm. The average particle size of the metal oxide particles can be derived, for example, by the following method: using a transmission electron microscope (TEM), a field emission transmission electron microscope (FE-TEM), a field emission scanning electron microscope (FE-SEM), etc. to magnify and observe the particles, randomly select, for example, 1000 particles, measure their maximum length, and find the arithmetic average, thereby calculating the average particle size of the metal oxide particles.
[0141] From the viewpoint of improving the stability of the metal oxide particles in the adhesive composition and improving the refractive index of the adhesive layer, the amount of the metal oxide particles added is preferably 10 to 50% by mass, more preferably 15 to 40% by mass, when the total amount of the adhesive composition is 100% by mass.
[0142] The adhesive composition may further contain a hydroxyl-containing (meth) acrylate. If such a composition is used, the adhesive force of the adhesive layer can be further improved. When the total amount of the adhesive composition is set to 100% by mass, the blending amount of the hydroxyl-containing (meth) acrylate is preferably 1% to 30% by mass, and more preferably 3% to 20% by mass.
[0143] F. Image display device
[0144] The optical laminate described in the above items A to E can be applied to image display devices. Therefore, the embodiments of the present invention also include image display devices using such optical laminates. As representative examples of image display devices, liquid crystal display devices and organic EL display devices can be listed. The image display device of the embodiment of the present invention is typically equipped with the optical laminate described in the above items A to E on its visual recognition side.
[0145] Example
[0146] The present invention is described in detail below by way of examples, but the present invention is not limited to these examples. The measuring methods and evaluation methods in the examples are as follows. Unless otherwise specified, "parts" and "%" in the examples are by weight.
[0147] (1) Curing shrinkage
[0148] The measurement was performed using a resin curing shrinkage measuring device (manufactured by Acroedge, product name "CUSTRON EU 201C") in accordance with JIS K6941. The details are as follows. In a cylindrical container with an inner diameter of 15 mm and a depth of 3 mm, a thickness of T 0The uncured adhesive used in the examples and comparative examples was placed in the container. The adhesive in the container was irradiated with 1000 mJ / cm 2 The adhesive is cured by ultraviolet light and the thickness T after curing is measured. D , the curing shrinkage is calculated by the following formula.
[0149] Curing shrinkage (%) = {(T 0 -T D ) / T 0}×100
[0150] (2) Thickness
[0151] The measurement was performed using an interferometer film thickness meter (manufactured by Otsuka Electronics Co., Ltd., “MCPD 9800”).
[0152] (3) Thickness deviation
[0153] For the laminate of polarizer / adhesive layer / first liquid crystal alignment cured layer in the optical laminate obtained in the examples and comparative examples, thickness mapping measurement was performed in a range of 10 cm×10 cm at a pitch of 1 mm using “USB4H09646” manufactured by Ocean Optics, Inc. The thickness difference at the point where the thickness difference between three adjacent points was the largest was taken as the thickness deviation.
[0154] (4) Linear unevenness
[0155] A conventional acrylic adhesive was placed on the second liquid crystal orientation cured layer side of the optical laminate obtained in the examples and comparative examples, and the optical laminate was bonded to a V3 reflector (manufactured by NEODIS) with the aid of the acrylic adhesive as a test sample. The test samples obtained were visually observed under a 3-wavelength fluorescent lamp and evaluated according to the following criteria.
[0156] 1: No linear unevenness was observed
[0157] 2: Slight linear unevenness is observed
[0158] 3: Linear unevenness was observed, but it was to a practically tolerable level.
[0159] 4: Linear unevenness is observed to a degree that is not acceptable in practical use
[0160] 5: Linear unevenness is obvious.
[0161] [Manufacturing Example 1: Preparation of Adhesive A for Laminating Polarizing Plate and Retardation Layer]
[0162] 40 parts of hydroxyethyl acrylamide (trade name "HEAA", manufactured by KJ Chemicals), 32 parts of acryloyl morpholine (trade name "ACMO", manufactured by KJ Chemicals), 25 parts of tripropylene glycol diacrylate (trade name "ARONIX M-220"), 1 part of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (trade name "Omnirad 819", manufactured by IGM Resins BV), 2 parts of 1-hydroxycyclohexyl phenyl ketone (trade name "Omnirad 184", manufactured by IGM Resins BV), and 1 part of diethylthioxanthone (trade name "KAYACURE DETX-S", manufactured by Nippon Kayaku Co., Ltd.) were stirred at 50° C. for 1 hour to prepare an adhesive A.
[0163] [Manufacturing Example 2: Preparation of Adhesive B for Laminating Polarizing Plate and Retardation Layer]
[0164] 10 parts of hydroxyethyl acrylamide (trade name "HEAA", manufactured by KJ Chemicals), 4 parts of 2-acetoacetoxyethyl methacrylate (trade name "AAEM", manufactured by Mitsubishi Chemicals), 60 parts of acryloylmorpholine (trade name "ACMO", manufactured by KJ Chemicals), 11 parts of tripropylene glycol diacrylate (trade name "Aronix M-220"), 1 part of 4-vinylphenylboric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), 10 parts of acrylic oligomer (trade name "ARUFON UP-1190", manufactured by Toagosei Co., Ltd.), 1 part of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (trade name "Omnirad 819", manufactured by IGM Resins BV), 1 part of 1-hydroxycyclohexyl phenyl ketone (trade name "Omnirad 184", manufactured by IGM Resins BV) were prepared. BV Co., Ltd.) and 1 part of diethylthioxanthone (trade name "KAYACURE DETX-S", manufactured by Nippon Kayaku Co., Ltd.) were stirred at 50° C. for 1 hour to prepare an adhesive B.
[0165] [Manufacturing Example 3: Preparation of Adhesive C for Laminating Polarizing Plate and Retardation Layer]
[0166] 60 parts of OGSOL EA-F 5710 (manufactured by Osaka Gas Chemical Co., Ltd.), 10 parts of Placcel FA1DDM (manufactured by Daicel Co., Ltd.), 20 parts of acryloylmorpholine (trade name "ACMO", manufactured by KJ Chemicals Co., Ltd.), 5 parts of acrylic oligomer (trade name "ARUFON UP-1190", manufactured by Toagosei Co., Ltd.), 1 part of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (trade name "Omnirad 819", manufactured by IGM Resins BV), 2 parts of 1-hydroxycyclohexyl phenyl ketone (trade name "Omnirad 184", manufactured by IGM Resins BV) and 2 parts of diethylthioxanthone (trade name "KAYACURE DETX-S", manufactured by Nippon Kayaku Co., Ltd.) were stirred at 50° C. for 1 hour to prepare an adhesive C.
[0167] [Example 1]
[0168] 1. Preparation of polarizer
[0169] 1-1. Preparation of polarizer
[0170] As the thermoplastic resin substrate, a long amorphous polyethylene terephthalate copolymer film (thickness: 100 μm) having a Tg of about 75° C. was used, and one surface of the resin substrate was subjected to a corona treatment.
[0171] 13 parts by weight of potassium iodide was added to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER") in a ratio of 9:1, and the resulting substance was dissolved in water to prepare a PVA aqueous solution (coating solution).
[0172] The PVA aqueous solution was applied to the corona-treated surface of the resin substrate and dried at 60° C. to form a PVA-based resin layer having a thickness of 13 μm, thereby producing a laminate.
[0173] The obtained laminate was uniaxially stretched to 2.4 times in the longitudinal direction (length direction) in an oven at 130° C. (in-air auxiliary stretching treatment).
[0174] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).
[0175] Next, the film was immersed in a dyeing bath (an iodine aqueous solution obtained by mixing iodine and potassium iodide at a weight ratio of 1:7 per 100 parts by weight of water) at a liquid temperature of 30° C. for 60 seconds while adjusting the concentration so that the single body transmittance (Ts) of the polarizer finally obtained would be a desired value (dyeing treatment).
[0176] Next, the sample was immersed in a crosslinking bath (boric acid aqueous solution prepared by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).
[0177] Then, while the laminate is immersed in an aqueous boric acid solution (boric acid concentration 4 wt%, potassium iodide concentration 5 wt%) at a liquid temperature of 70°C, it is uniaxially stretched (underwater stretching treatment) in the longitudinal direction (length direction) between rollers with different peripheral speeds so that the total stretching ratio becomes 5.5 times.
[0178] Then, the laminated body was immersed in a cleaning bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment).
[0179] Thereafter, the film was dried in an oven maintained at approximately 90° C. while being brought into contact with a SUS heating roll maintained at a surface temperature of approximately 75° C. (drying shrinkage treatment).
[0180] In this manner, a polarizer having a thickness of about 5 μm was formed on the resin substrate, thereby obtaining a polarizing plate having a structure of resin substrate / polarizer. The single-unit transmittance Ts of the polarizer was 43.3%.
[0181] 1-2. Preparation of polarizing film
[0182] The HC-COP film is attached to the surface of the obtained polarizer (the surface on the opposite side to the resin substrate) by means of an ultraviolet curing adhesive. It should be noted that the HC-COP film is a film having an HC layer (thickness 4 μm) formed on a cycloolefin resin (COP) film (thickness 25 μm), and is attached in such a way that the COP film becomes the polarizer side. In addition, the Re (550) of the COP film is 135 nm. Next, the resin substrate is peeled off to obtain a polarizing plate having a structure of HC layer / COP film (protective layer) / polarizer.
[0183] 2. Fabrication of phase difference layer
[0184] A photopolymerizable liquid crystal compound showing a nematic liquid crystal phase ("Paliocolor LC 242" manufactured by BASF, the following chemical formula) was dissolved in cyclopentanone to prepare a solution having a solid content concentration of 30% by weight. A surfactant ("BYK-360" manufactured by BYK-Chemie) and a photopolymerization initiator ("Omnirad 907" manufactured by IGM Resins) were added to the solution to prepare a liquid crystal composition solution. The amount of surfactant and polymerization initiator added was set to 0.01 parts by weight and 3 parts by weight, respectively, relative to 100 parts by weight of the photopolymerizable liquid crystal compound. As a substrate, a biaxially stretched norbornene film ("ZEONOR FILM" manufactured by ZEON Japan, thickness 33μm, Re(550) = 135nm) was prepared. The above-mentioned liquid crystal composition was applied to the substrate using a rod coater in a manner such that Re(550) became 240nm, and the liquid crystal was oriented by heating at 100°C for 3 minutes. After cooling to room temperature, the samples were irradiated in a nitrogen atmosphere with a cumulative light intensity of 400 mJ / cm 2 The substrate was photocured by ultraviolet light to obtain a laminate having a structure of a substrate / first liquid crystal orientation solidification layer. The first liquid crystal orientation solidification layer was horizontally oriented (homogeneous orientation) and had a thickness of 1.7 μm. A laminate of a substrate / second liquid crystal orientation solidification layer (horizontally oriented, 0.92 μm thick, Re (550) = 130 nm) was obtained in the same manner as above except that the coating thickness was changed.
[0185]
[0186] 3. Fabrication of optical laminates
[0187] After the first liquid crystal orientation solidification layer is bonded to the surface of the polarizer of the polarizer with the help of the adhesive A (thickness 1.2 μm) of Manufacturing Example 1, the substrate is peeled off. Next, the second liquid crystal orientation solidification layer is bonded to the surface of the first liquid crystal orientation solidification layer with the help of an acrylic adhesive (5 μm, refractive index 1.47), and the substrate is peeled off to obtain an optical laminate having a structure of polarizer / adhesive layer / first liquid crystal orientation solidification layer / interlayer adhesive layer / second liquid crystal orientation solidification layer. In the optical laminate, the angle formed by the transmission axis of the polarizer of the polarizer and the slow axis of the first liquid crystal orientation solidification layer is 15°, and the angle formed by the transmission axis of the polarizer of the polarizer and the slow axis of the second liquid crystal orientation solidification layer is 75°. The obtained optical laminate is provided for the above-mentioned "linear unevenness" evaluation. The results are shown in Table 1.
[0188] [Examples 2 to 12 and Comparative Examples 1 to 6]
[0189] An optical layered body was obtained in the same manner as in Example 1 except that the configuration of the adhesive layer was changed as shown in Table 1. The obtained optical layered body was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0190] [Table 1]
[0191]
[0192] Industrial Applicability
[0193] The optical laminate according to the embodiment of the present invention can be suitably used in image display devices (typically, liquid crystal display devices and organic EL display devices).
Claims
1. An optical laminate comprising a polarizing plate including a polarizer and a phase difference layer laminated on the polarizing plate via an adhesive layer, The phase difference layer includes a first liquid crystal alignment solidified layer and a second liquid crystal alignment solidified layer in order from the polarizing plate side. The phase difference layer as a whole has a circular polarization function or an elliptical polarization function, and has a relationship of Re(450)<Re(550)<Re(650). The thickness variation of the adhesive layer in a region of 10 cm×10 cm was 0.16 μm or less.
2. An optical laminate comprising a polarizing plate including a polarizer and a phase difference layer laminated on the polarizing plate via an adhesive layer, The phase difference layer includes a first liquid crystal alignment solidified layer and a second liquid crystal alignment solidified layer in order from the polarizing plate side. The phase difference layer as a whole has a circular polarization function or an elliptical polarization function, and has a relationship of Re(450)<Re(550)<Re(650). When the thickness of the adhesive layer is T (μm) and the cure shrinkage rate of the adhesive constituting the adhesive layer is S (%), T×S≤17 is satisfied.
3. The optical laminate according to claim 2, wherein: The thickness variation of the adhesive layer in a region of 10 cm×10 cm was 0.16 μm or less.
4. The optical layered body according to any one of claims 1 to 3, wherein The adhesive layer is composed of an active energy ray-curable adhesive.
5. The optical layered body according to any one of claims 1 to 3, wherein The thickness of the first liquid crystal alignment solidified layer is 1.7 μm or less. 6 . An image display device comprising the optical layered body according to claim 1 .
Citation Information
Patent Citations
Liq. crystalline (LC) material
DE19504224A1
Novel polymerizable liquid crystalline compounds
DE4408171A1
Liquid crystalline reticulated polysiloxanes
EP0066137A1
Picture display cell, method of forming an orientation layer on a substrate of the picture display cell and monomeric compounds for use in the orientation layer
EP0261712A1
Liquid crystal polyorganosiloxanes containing (meth)acryloxy groups
EP0358208A2